1992
DOI: 10.1073/pnas.89.22.10563
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a negative regulatory function for steroid receptors.

Abstract: This report describes the identification of a negative regulator of estrogen and progesterone receptor function. Using a reconstituted estrogen-responsive transcription system in Saccharomyces cereviswae, we have identified a "repressor function," which when mutated, increases the transcriptional activity of the estrogen and progesterone receptors.In the case of the estrogen receptor this mutation increases the sensitivity of estrogen-mediated activation by at least four orders of magnitude. Analysis of deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 26 publications
2
46
0
Order By: Relevance
“…An interesting activity of the SSN6 protein has been reported recently by McDonnell et al (1992). By use of a reconstituted estrogen-responsive transcription system in yeast, those investigators found that SSN6 acts as a repressor of transcription by the TAF1 domain of the estrogen receptor.…”
Section: Repression Of Other Genes By Ssn6 and Tupimentioning
confidence: 88%
See 1 more Smart Citation
“…An interesting activity of the SSN6 protein has been reported recently by McDonnell et al (1992). By use of a reconstituted estrogen-responsive transcription system in yeast, those investigators found that SSN6 acts as a repressor of transcription by the TAF1 domain of the estrogen receptor.…”
Section: Repression Of Other Genes By Ssn6 and Tupimentioning
confidence: 88%
“…By use of a reconstituted estrogen-responsive transcription system in yeast, those investigators found that SSN6 acts as a repressor of transcription by the TAF1 domain of the estrogen receptor. Although a model in which mutation of SSN6 leads to global alterations in chromatin structure was disfavored by McDonnell et al (1992), the possibility remains that such mutations lead to changes in the chromatin structures of a subset of genes to which the SSN6 protein is specifically recruited. Thus, if a m a m m a l i a n counterpart to the SSN6 protein exists, it will be worthwhile to investigate the possibility that such a protein acts in part via regulation of chromatin structure in m a m m a l i a n cells.…”
Section: Repression Of Other Genes By Ssn6 and Tupimentioning
confidence: 99%
“…Transcription activation functions in general have been proposed to act as inhibitors (50), and reduced concentrations of SPT6, which is active in yeast and mammalian cells, caused a left shift in the estrogen dose-response curve (51). Genetic deletion of the yeast repressor SSN6 also caused increased percentages of agonist activity for antiestrogens, but not antiprogestins, and a Ն10-fold left shift in the dose-response curve for agonists bound to estrogen or progesterone receptors in yeast (52). Unfortunately, no mammalian homologues of SSN6 have yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…In most cell and promoter contexts, the transcriptional activity of steroid hormone receptors appears to require the functional synergy between the amino and carboxyl termini of each individual receptor (6,39,40,46,53,57). This synergy occurs as a consequence of an agonist-dependent association between the amino and carboxyl AFs of ER␣ (31), the androgen receptor (5,14,27), and hPRA and hPRB, respectively (54).…”
Section: Discussionmentioning
confidence: 99%